Detection of autotrophic verrucomicrobial methanotrophs in a geothermal environment using stable isotope probing - Sharp, Christine; Stott, Matthew; Dunfield, Peter (Frontiers in Microbiology, 2012)
Genomic analysis of the methanotrophic verrucomicrobium “Methylacidiphilum infernorum” strain V4 has shown that most pathways conferring its methanotrophic lifestyle are similar to those found in proteobacterial methanotrophs. However, due to the large sequence divergence of its methane monooxygenase-encoding genes (pmo), ‘universal’ pmoA polymerase chain reaction (PCR) primers do not target these bacteria. Unlike proteobacterial methanotrophs, “Methylacidiphilum” fixes carbon autotrophically, and uses methane only for energy generation. As a result, techniques used to detect methanotrophs in the environment such as 13CH4-stable isotope probing (SIP) and pmoA-targeted PCR do not detect verrucomicrobial methanotrophs, and they may have been overlooked in previous environmental studies. We developed a modified SIP technique to identify active methanotrophic verrucomicrobia in the environment by labelling with 13CO2 and 13CH4, individually and in combination. Testing the protocol in “M. infernorum” strain V4 resulted in assimilation of 13CO2 but not 13CH4, verifying its autotrophic lifestyle. To specifically detect methanotrophs (as opposed to other autotrophs) via 13CO2-SIP, a quantitative PCR (qPCR) assay specific for verrucomicrobial-pmoA genes was developed and used in combination with SIP. Incubation of an acidic, high-temperature geothermal soil with 13CH4 + 12CO2 caused little shift in the density distribution of verrucomicrobial-pmoA genes relative to controls. However, labelling with 13CO2 in combination with 12CH4 or 13CH4 induced a strong shift in the distribution of verrucomicrobial-pmoA genes towards the heavy DNA fractions. The modified SIP technique demonstrated that the primary methanotrophs active in the soil were autotrophs and belonged to the Verrucomicrobia. This is the first demonstration of autotrophic, non-proteobacterial methanotrophy in situ, and provides a tool to detect verrucomicrobial methanotrophs in other ecosystems.